Tailoring Second Harmonic Generation via Strong Coupling in a One‐Dimensional Photonic Crystal Heterostructure - Ying Zhu; Ruize Ma; Anlong Dong; Hangsheng Xu; Chunhua Wang; Meng Qin; Jianqiang Liu; Hongju Li (Advanced Photonics Research)
Controlling harmonic generation is crucial for nonlinear optics and nanophotonic devices. Herein, a 1D photonic crystal heterostructure is theoretically proposed comprising a metal film, a lithium niobate layer, and a distributed Bragg reflector with a defect layer. The Tamm state and the defect state for dual‐band second‐harmonic generation (SHG) enhancement simultaneously are numerically investigated. Finite‐element method simulations indicate that SHG efficiencies based on Tamm plasmons and the defect state are 6.85 × 10−6 and 3.28 × 10−4, respectively. Intriguingly, the strong coupling between the defect state and Tamm plasmons enables spatial energy exchange, leading to the SHG switching between them. In the strong coupling region with Rabi splitting energy up to 5.5 meV, the SHG conversion efficiency reaching 5 × 10−5 is observed for both two new hybridized states. During the entire anticrossing Rabi splitting process, the SHG efficiency difference between two resonances can be modulated by up to two orders of magnitude. The coupling strength between two resonances is adjusted by varying the position of the defect layer. Simulation results are consistent with the coupled oscillator model. This work not only offers a platform for studying nonlinear frequency conversion but also establishes a new method of using strong coupling to tailor SHG.